2011
DOI: 10.1016/j.jval.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Care for Dementia Patients in Community Setting: An Analysis for Mild and Moderate Disease Stage

Abstract: Due to valued informal care, costs of care for community-living patients with moderate dementia are significantly higher than for patients with mild dementia. Informal care is a non-cash item saving expenditures for professional care. To relieve social security system and family caregivers as well as to allow dementia patients to stay at home as long as possible, concepts fostering community-based dementia care and support to family caregivers need to be further developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 39 publications
10
96
1
2
Order By: Relevance
“…In this analysis, diagnosed patients had more comorbidities, which could cause a higher need of differentiated outpatient physician treatments. However, less treatment by outpatient physicians in the progression of dementia diseases is out of line with published studies, which frequently state constant or higher outpatient physician treatments for more cognitively impaired PWD (Leicht et al, 2011;Schwarzkopf et al, 2011). It is questionable whether a formal diagnosis for dementia leads to inadequate outpatient treatment or if the outpatient treatment is managed more effectively to reduce the patient's burden after receiving a formal diagnosis of dementia.…”
Section: Differences In Resource Utilization and Costs Depending On Dmentioning
confidence: 96%
“…In this analysis, diagnosed patients had more comorbidities, which could cause a higher need of differentiated outpatient physician treatments. However, less treatment by outpatient physicians in the progression of dementia diseases is out of line with published studies, which frequently state constant or higher outpatient physician treatments for more cognitively impaired PWD (Leicht et al, 2011;Schwarzkopf et al, 2011). It is questionable whether a formal diagnosis for dementia leads to inadequate outpatient treatment or if the outpatient treatment is managed more effectively to reduce the patient's burden after receiving a formal diagnosis of dementia.…”
Section: Differences In Resource Utilization and Costs Depending On Dmentioning
confidence: 96%
“…These findings are similar to those from earlier studies that reported higher healthcare resource utilization and costs for individuals with Alzheimer's disease and dementia when compared with individuals without these conditions. [31][32][33][34] Individuals diagnosed with dementia are more likely to also be diagnosed with other comorbidities, 35 and to report greater difficulties in instrumental activities of daily living. 36 As a result, individuals with dementia may tend to use more LTC services and therefore incur higher LTC expenditure than non-dementia individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Available cost studies from several European countries show a strong positive relationship between disease severity and total costs of care [1,[3][4][5][6][7][8]. Informal care costs form the major component of societal costs for community-dwelling AD dementia patients [8][9][10][11], and the cost of institutional care is the other main cost driver in the long-term care of patients with AD dementia [12].…”
Section: Introductionmentioning
confidence: 99%